Identification and Validation of Ferroptosis-Related Genes in Sevoflurane-Induced Hippocampal Neurotoxicity. (4th October 2022) - Miao, Mengrong; Wang, Yangyang; Zeng, Shuang; Han, Yaqian; Zhu, Ruilou; Yu, Pengfei; Yang, Yitian; Fu, Ningning; Li, Ningning; Sun, Mingyang; Zhang, Jiaqiang
Abstract : Background . Sevoflurane is one of the most popular inhalational anesthetics during perioperative period but presenting neurotoxicity among pediatric and aged populations. Recent experiments in vivo and in vitro have indicated that ferroptosis may contribute to the neurotoxicity of sevoflurane anesthesia. However, the exact mechanism is still unclear. Methods . In current study, we explored the differential expressed genes (DEGs) in HT-22 mouse hippocampal neuronal cells after sevoflurane anesthesia using RNA-seq. Differential expressed ferroptosis-related genes (DEFRGs) were screened and analyzed by Gene Ontology (GO) and pathway enrichment analysis. Protein-to-protein interaction (PPI) network was constructed by the Search Tool for the Retrieval of Interacting Genes (STRING). Significant modules and the hub genes were identified by using Cytoscape. The Connectivity Map (cMAP) was used for screening drug candidates targeting the identified DEFRGs. Potential TF-gene network and drug-gene pairs were established towards the hub genes. In final, we validated these results in experiments. Results . A total of 37 ferroptosis-related genes (18 upregulated and 19 downregulated) after sevoflurane exposure in hippocampal neuronal cells were finally identified. These differentially expressed genes were mainly involved into the biological processes of cellular response to oxidative stress. Pathway analysis indicated that these genes were involved in ferroptosis, mTOR signaling pathway, and longevity-regulating pathway. PPI network was constructed. 10 hub genes including Prkaa2, Chac1, Arntl, Tfrc, Slc7a11, Atf4, Mgst1, Lpin1, Atf3, and Sesn2 were found. Top 10 drug candidates, gene-drug networks, and TFs targeting these genes were finally identified. These results were validated in experiments. Conclusion . Our results suggested that ferroptosis-related genes play roles in sevoflurane anesthesia-related hippocampal neuron injury and offered the hub genes and potential therapeutic agents for investigating and treatment of this neurotoxicity after sevoflurane exposure. Finally, therapeutic effect of these drug candidates and function of potential ferroptosis targets should be further investigated for treatment and clarifying mechanisms of sevoflurane anesthesia-induced neuron injury in future research.